UWB Technology and its Applications - Kocur, Dusan (IntechOpen, 2019)
Ultra-wideband (UWB) technology is a radio technology that uses electromagnetic waves with a very low power spectral density occupying a bandwidth of more than 25% of a centre frequency, or more than 0.5GHz, for short-range remote sensing, high-bandwidth communications or object positioning. The detailed analyses of state-of-the-art UWB technology has shown that this technology is very interesting and promising with a great application potential. Following these facts, our book attempts to present current and emerging trends in research and development of UWB systems. The book is focused on basic components of UWB systems such as antennas, filters, photonic approach for signal processing methods, as well as on some applications of UWB systems (human target analysis, cancer detection).